Multidimensional exploration of landscape preferences in rural squares: an empirical inquiry relying on electroencephalography, eye - tracking and Perceived Restorative Scale - Hongguo Ren; Zhenyu Li; Ying Liu; Minqi Shi (Journal of Asian Architecture and Building Engineering, 2025)
In order to objectively evaluate the impact of the rural square landscape on human physiological and emotional changes, the author utilized a combination of electroencephalography (EEG), eye-tracking technology, and the Perceived Restorative Scale to study user preference for regular and free-form rural square landscapes. The results show that, in the free-form square landscape, participants exhibited significantly higher α/β ratios in the temporal lobe region, indicating a greater potential for neural relaxation. Eye-tracking data also demonstrated a stronger user preference for this landscape type. Further comparative analysis based on Areas of Interest and heatmaps revealed that soft landscape elements play a central role in guiding visual attention and stimulating cognitive processing. In contrast, hard landscape elements primarily enhance the rhythm of visual search, while landscape facilities elements serve as auxiliary features in attention capture and cognitive engagement. This study provides new perspectives and methods for studying landscape preference in rural squares, fills gaps in understanding neural mechanisms, and provides a scientific basis for the planning and design of rural squares, which is of great significance in promoting the development of rural public space.